Faktor-Faktor Yang Mempengaruhi Transfer Pricing Pada Perusahaan Manufaktur - Erica; Ngadiman (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2022)
This research aims to obtain empirical evidence about the effect of Tax, Bonus Mechanism, Debt Convenant, and Tunneling Incentive towards Transfer Pricing. This research uses secondary data obtained from Indonesia Stock Exchange (IDX). The population of this research is all manufacture sector companies listed on the IDX in the 2015-2019 period. This research is conducted with a sample size of 50 data that were processed using IBM Statistical Package for the Social Sciences (SPSS) ver 25.0 with multiple linear regression analysis method. The results of this research found that Tax has a significant positive effect on Transfer Pricing. Meanwhile Bonus Mechanism has no significant effect on Transfer Pricing. In addition, Debt Convenant and Tunneling Incentive have a significant negative effect on Transfer Pricing.